Ursodeoxycholic acid modulates E2F-1 and p53 expression through a caspase-independent mechanism in transforming growth factor beta 1-induced apoptosis of rat hepatocytes - Sola, S (2015)
Transforming growth factor beta1 (TGF-beta1)-induced hepatocyte apoptosis is associated with activation of E2F transcription factors and p53 stabilization through Mdm-2, thus potentially modulating a number of target genes. In previous studies, we have sh